Building Long-Term Relationships with Customers through Effective Communication - Ibnu Agung Hermawan; Saprida Saprida; Havis Aravik; Ahmad Tohir (Penerbit dan Percetakan CV.Picmotiv, 2026)
Rapid technological developments and changes in the business environment require companies to maintain sustainable relationships with customers. Effective communication is one of the key factors in building trust, increasing customer satisfaction, and fostering customer loyalty. This article aims to examine the role of effective communication in building long-term relationships with customers. The article employs a literature review method by utilizing various relevant sources related to business communication and customer relationship management. The findings indicate that clear, open, and responsive communication can strengthen the relationship between companies and customers and support business sustainability amid increasingly dynamic competition. Therefore, effective communication serves as an important strategy for companies in maintaining customer trust and loyalty.